SISTEM REKOMENDASI PEMILIHAN DOSEN PEMBIMBING SKRIPSI MENGGUNAKAN METODE SMART DI UNIVERSITAS BANTEN JAYA - Raden Kania; Reni Febriani; Tifani Intan Solihati; Nur Hidayanti; Achmad Radimas (Jurnal Sistem Informasi dan Informatika (Simika), 2026)
The appointment of a lecturer tutoring the thesis at Banten Jaya University specifically has a computer science faculty. This faculty has five curricula. In the study program of Computer Engineering, the selection of a lecturer tutor for the thesis by the head of the study program, which in the process is done by determining directly by the head of the study program because the appointment of the tutor is determined through the meeting, because of the number of students who follow the theses then head of the study program takes a long enough time to choose the lecturer to each student. Then a decision-making system is needed so that students can identify tutoring lecturers by calculating based on criteria such as competence, linearity, functional post, and quota of lecturers. This study aims to build a decision support system that can give recommendations and determine the tutor of the thesis. Based on that, the research has developed a system with decision-making techniques using the Simple Multi-Attribute Rating Technique (SMART) method. In contrast, the system development aids use the waterfall model and the Unified Modeling Language (UML) as system design aids. The result is a decision-support system for the recommendation of lecturer tutoring a thesis based on the Website, from the results of the tests carried out removed the system, the system can give the recommendation lecturer to the student based on calculations made using the SMART method, the system also provides features for the selection of lecturers tutors in the thesis.